(untitled) (Third Sector Social Economic Review, 2026)
The purpose of this study is to determine the mediating role of informal relationships in the effect of workplace friendship on organizational cronyism. To this end, a survey was conducted on employees working in public institutions in the province of Kırşehir. There are a total of 6,010 public employees in Kırşehir, and the sample consists of 386 employees selected from among these individuals. In this study, which adopted a quantitative research design, the workplace friendship scale, organizational cronyism scale, and informal relationships scale were used as data collection tools. The collected data were analyzed using the SPSS 26.00 software package. According to the analysis results, informal relationships were found to play a mediating role in the effect of workplace friendship on organizational cronyism. In addition, workplace friendship has a significant effect on organizational cronyism. On the other hand, organizational cronyism has a significant effect on informal relationships.